Satisfaction of patients suffering from type 2 diabetes and/or hypertension with care offered in family medicine clinics in Mexico Satisfacción en pacientes con diabetes mellitus o hipertensión arterial atendidos en clínicas de medicina familiar en México - Svetlana Vladislavovna Doubova; Ricardo Pérez-Cuevas; Maribel Zepeda-Arias; Sergio Flores-Hernández (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE:To evaluate the satisfaction and the factors related to dissatisfaction in patients suffering from type 2 diabetes and/or hypertension with care offered in family medicine clinics. MATERIAL AND METHOD: A secondary data analysis was conducted. Main outcome measures were two indices of satisfaction: family doctor-patient relationship (FDPR) and clinic organizational arrangements (OA). RESULTS: Approximately half of patients (n=1 323) were satisfied with care. In the FDPR index the items "kindness of the family doctor" (FD) scored high, while the lowest score was for the items: "the FD allows the patient to give an opinion about his/her treatment," "the patient understands the information" and "the FD spends enough time on the consultation." As for satisfaction with OA, the items "cleanliness of the clinic" and "ease of administrative procedures" obtained the lowest scores. In the logistic regression analysis the covariate "negative self-rated health" and "type of institution" were associated with dissatisfaction. CONCLUSIONS:There are aspects of the FDPR and OA that reveal dissatisfaction of patients with chronic conditions. OBJETIVO:Analizar la satisfacción y los factores relacionados con insatisfacción en pacientes con diabetes mellitus (DM) o hipertensión arterial (HTA) atendidos en clínicas de medicina familiar (MF). MATERIAL Y MÉTODOS:Se realizó análisis secundario de datos. Las variables de resultado fueron dos índices de satisfacción: relación médico familiar-paciente (RMFP) y aspectos organizacionales (AO). RESULTADOS:Aproximadamente la mitad de los pacientes (n=1 323) estuvieron satisfechos. Para la RMFP, "la amabilidad del MF" obtuvo la mayor calificación, y la más baja fue para "el MF permite la opinión del paciente sobre los tratamientos", "comprensión de la información" y "tiempo que el MF dedica al paciente". Para satisfacción con AO, "la limpieza de la clínica" y "fácil solución de los trámites administrativos" calificaron más bajo. En la regresión múltiple, la "autopercepción negativa de la salud" y "tipo de la institución" fueron relacionados con insatisfacción. CONCLUSIÓN: Existen aspectos de RMFP y AO que provocan mayor insatisfacción en los pacientes crónicos y requieren mayor atención.